Hear #metoo in India : news, social media, and anti-rape and sexual harassment activism - Guha, Pallavi (Rutgers University Press, 2021)
This book examines the role media platforms play in anti-rape and sexual harassment activism in India. Including 75 interviews with feminist activists and journalists working across India, it proposes a framework of agenda-building and establishes a theoretical framework to examine media coverage of issues in the digitally emerging Global South.